1986
DOI: 10.1111/j.1365-2125.1986.tb05235.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of diabetes mellitus, exercise, and single doses of biguanides upon lactate metabolism in man.

Abstract: 1 The polymorphism of phenformin oxidation has been investigated in 103 non-insulindependent (Type II) diabetics. The frequency distribution was clearly bimodal and 14 poor metabolisers were identified. The frequency of the recessive allele (0.369) was not significantly different from that found previously in non-diabetics. 2 Six of the extensive metabolisers of phenformin were matched for age, sex and oxidiser phenotype with non-diabetic controls. All subjects underwent a standard 3-min exercise test, using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2

Year Published

1987
1987
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 16 publications
0
3
2
Order By: Relevance
“…Plasma lactate concentration was higher in the metformin group after aerobic exercise compared with the glibenclamide and control groups. In contrast to other studies, which showed little or no difference in lactate levels during exercise in diabetic patients taking metformin and healthy subjects [41–43], our results suggest than metformin prevented the fall in plasma lactate normally seen after exercise, perhaps by interfering with lactate clearance. One possible explanation is that metformin inhibits hepatic gluconeogenesis, reducing the utilization and plasma extraction of several substrates, including lactate [18,19].…”
Section: Discussioncontrasting
confidence: 99%
“…Plasma lactate concentration was higher in the metformin group after aerobic exercise compared with the glibenclamide and control groups. In contrast to other studies, which showed little or no difference in lactate levels during exercise in diabetic patients taking metformin and healthy subjects [41–43], our results suggest than metformin prevented the fall in plasma lactate normally seen after exercise, perhaps by interfering with lactate clearance. One possible explanation is that metformin inhibits hepatic gluconeogenesis, reducing the utilization and plasma extraction of several substrates, including lactate [18,19].…”
Section: Discussioncontrasting
confidence: 99%
“…Despite higher lactate levels in the M group at fasting, our date did no corroborate the concern that this medication could induce hyperlactacidaemia in hypoxic conditions [16,17]. Previous studies examining the effect of biguanides during exercise (not maximal) in diabetic and healthy subjects have shown little or no difference in lactate levels [46–48].…”
Section: Discussioncontrasting
confidence: 80%
“…However, the acute metformin dose on the experimental days in both the A‐MES and ST‐MES induced both higher resting and exercised induced plasma lactate compared to placebo. To our knowledge only a single study in addition to the present has reported a metformin effect on resting plasma lactate content (Boule et al, ) while some (Boule et al, ; Malin et al, ; Sharoff et al, ) but not all (Cunha et al, , ; Fletcher, Hirji, Kuhn, Alexander, & Mucklow, ; Gudat et al, ) studies have observed an effect in combination with exercise. Although muscle lactate content increased during exercise, this increase was similar in the metformin and placebo trials, suggesting that the metformin‐induced increase in plasma lactate is not of muscle origin.…”
Section: Discussionmentioning
confidence: 56%